UPAYA MENINGKATKAN KREATIVITAS ANAK MELALUI PEMBELAJARAN STEAM DENGAN MEDIA LOOSE PART PADA ANAK KELOMPOK A TK PERTIWI BANTARWUNI TAHUN PELAJARAN 2020/2021 - Andriyani, Dwi (Jurnal Analisis Pendidikan Sosial, 2025)
The purpose of this study is to describe the process and learning outcomes through learning STEAM (Sciense Technology Engineering Art and Mathematich) using Loose Part media which can increase the creativity of group A children at Pertiwi Bantarwuni Kindergarten, Kembaran District, Banyumas Regency, for the Academic Year 2020/2021 as many as 15 students. The method used in this research is Kemmis and Mc Taggart's Class Action Research which includes four stages, namely planning, observation, action and reflection and decision making for the development of activities and subsequent actions. Data collection techniques using observation, notes and documentation. From the results of research in the pre-cycle through the test of creativity ability indicators, students' abilities showed 33% completeness. Then it increased in cycle I to cycle II, namely cycle I (60%), cycle II (86%). The conclusion of this study is that through STEAM learning with Loose Part media, it can increase the creativity of Pertiwi Bantarwuni Kindergarten children in Group A for the 2020/2021 Academic Year. This study consisted of two cycles, each cycle consisting of 4 meetings. The data analysis technique used is qualitative and quantitative data analysis. Qualitative data analysis by analyzing data from observations, interviews and documentation during the study. Quantitative data analysis uses a data processing approach through statistical methods to explain the level of success in learning in Cycle 1 and Cycle 2. The results of this study indicate an increase in early childhood creativity through STEAM learning with Loose Part media.